An Analysis of Siyasah Tasyri’iyah on Village Head Tenure: A Comparative Study of Law No. 3 of 2024 and Law No. 11 of 2006 - Muhajir Samsuar; Saifullah Yunus; Nurul Fithria (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2026)
This study examines the regulation of village head tenure from the perspective of siyasah tasyri’iyah through a comparative analysis of two legal frameworks: the tenure provisions for village heads under Law No. 3 of 2024 on Villages and the tenure provisions for keuchik under Law No. 11 of 2006 on the Government of Aceh. The study aims to explore the underlying reasons for differences in tenure regulation at the national level and within Aceh’s special autonomous framework, as well as to assess their conformity with the principles of justice (‘adl), public welfare (maslahah), and maqashid al-shari‘ah in siyasah tasyri’iyah. Unlike previous studies, this research not only examines normative legal aspects but also links the harmonization of national law and Aceh’s special autonomy with siyasah tasyri’iyah values and recent Constitutional Court decisions. Employing a normative legal approach based on library research of statutes, legal documents, and relevant academic literature, the study finds that Law No. 3 of 2024 establishes an eight-year tenure to promote governmental stability and sustainable village development, whereas Law No. 11 of 2006 stipulates a six-year tenure as a form of lex specialis that ensures leadership continuity while facilitating regeneration in accordance with local customs and Islamic values. The Constitutional Court has affirmed that the six-year tenure remains applicable in Aceh. Accordingly, the regulation of village head tenure in Aceh is considered more consistent with siyasah tasyri’iyah principles, as it maintains a balance between governmental stability, public welfare, the control of power, and opportunities for leadership regeneration.